Testing the methodology for a dosimetric end-to-end audit of IMRT/VMAT: results of IAEA multicentre and national studies - Wesolowska, Paulina; Georg, Dietmar; Lechner, Wolfgang; Kazantsev, Pavel; Bokulic, Tomislav; Tedgren, Asa Carlsson; Adolfsson, Emelie; Campos, Anna Maria; Alves, Victor Gabriel Leandro; Suming, Luo; Hao, Wu; Ekendahl, Daniela; et al. (Acta oncologica, 2019)
Introduction: Within an International Atomic Energy Agency (IAEA) co-ordinated research project (CRP), a remote end-to-end dosimetric quality audit for intensity modulated radiation therapy (IMRT)/ volumetric arc therapy (VMAT) was developed to verify the radiotherapy chain including imaging, treatment planning and dose delivery. The methodology as well as the results obtained in a multicentre pilot study and national trial runs conducted in close cooperation with dosimetry audit networks (DANs) of IAEA Member States are presented.Material and methods: A solid polystyrene phantom containing a dosimetry insert with an irregular solid water planning target volume (PTV) and organ at risk (OAR) was designed for this audit. The insert can be preloaded with radiochromic film and four thermoluminescent dosimeters (TLDs). For the audit, radiotherapy centres were asked to scan the phantom, contour the structures, create an IMRT/VMAT treatment plan and irradiate the phantom. The dose prescription was to deliver 4 Gy to the PTV in two fractions and to limit the OAR dose to a maximum of 2.8 Gy. The TLD measured doses and film measured dose distributions were compared with the TPS calculations.Results: Sixteen hospitals from 13 countries and 64 hospitals from 6 countries participated in the multicenter pilot study and in the national runs, respectively. The TLD results for the PTV were all within ±5% acceptance limit for the multicentre pilot study, whereas for national runs, 17 participants failed to meet this criterion. All measured doses in the OAR were below the treatment planning constraint. The film analysis identified seven plans in national runs below the 90% passing rate gamma criteria.Conclusion: The results proved that the methodology of the IMRT/VMAT dosimetric end-to-end audit was feasible for its intended purpose, i.e., the phantom design and materials were suitable; the phantom was easy to use and it was robust enough for shipment. Most importantly the audit methodology was capable of identifying suboptimal IMRT/VMAT delivery.
Keywords: Quality Assurance, Health Care; mezinárodní agentury; Feasibility Studies; Tomography, X-Ray Computed; Radiometry; fantomy radiodiagnostické; lidé; kritické orgány; Radiotherapy Planning, Computer-Assisted; Pilot Projects; celková dávka radioterapie; pilotní projekty; radiometrie; International Agencies; Organs at Risk; zajištění kvality zdravotní péče; studie proveditelnosti; plánování radioterapie pomocí počítače; Phantoms, Imaging; revize kvality lékařské péče; jaderná energie; Nuclear Energy; počítačová rentgenová tomografie; Radiotherapy Dosage; Medical Audit; radioterapie s modulovanou intenzitou; Radiotherapy, Intensity-Modulated; Humans